THE COMBINATION OF ENZYME AND SUBSTRATE : I. A METHOD FOR THE QUANTITATIVE DETERMINATION OF PEPSIN. II. THE EFFECT OF THE HYDROGEN ION CONCENTRATION. - Northrop, John H. (The Rockefeller University Press, 1919)
1. A quantitative method for the determination of pepsin is described depending on the change in conductivity of a digesting egg albumin solution. 2. The combination of pepsin with an insoluble substrate has been followed by this method. 3. The amount of pepsin removed from solution by a given weight of substrate is independent of the size of the particles of the substrate. 4. There is an optimum zone of hydrogen ion concentration for the combination of enzyme and substrate corresponding to the optimum for digestion. 5. It is suggested that the pepsin combines largely or entirely with the ionized protein.